Izbira in uporaba učnih medijev pri pouku glasbe - Kovačič, Bojan (Revija za elementarno izobraževanje, 2008)
This article presents how learning media is chosen and used in music classes. Special attention is given to the results of research done on the way learning media is used in classes. The aim of our research was to study the types of learning media used in student presentations for music education lessons and the influence of the different factors involved in choosing learning media. 105 fourth-grade elementary school students participated in our research, which took place during the 2007/08 school year at the Faculty of Education at the University of Maribor, Slovenia. The results show that during music classes students mostly use traditional learning media. When performing in the classroom they commonly use CD players, keyboards, rhythmic and melodie Orf instruments, textbooks and handbooks. None of the students use modern technology, including computer music programs and MIDI devises. During music classes most of the students use at least two forms of audio media. The media is used during the beginning of the central part of the lesson. We found that the choice of learning media used in music classes depends on the following factors: (1) learning content, (2) learning goals, and (3) age of the students.
Keywords: izobraževalna tehnologija; učni mediji; učni pripomočki; glasbena vzgoja; osnovne šole